1992
DOI: 10.1042/bj2830165
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the molecular mechanism involved in the activation of hyaluronan synthetase by platelet-derived growth factor in human mesothelial cells

Abstract: The molecular mechanism involved in the stimulation of hyaluronan synthetase in normal human mesothelial cells was investigated. Exposure of mesothelial cells to platelet-derived growth factor (PDGF)-BB stimulated hyaluronan synthetase activity, measured in isolated membrane preparations, as well as hyaluronan secretion into the medium. The effect on hyaluronan synthetase was maximal after 6 h of treatment. In contrast, the stimulatory effect of transforming growth factor-beta 1 reached a maximum after 24 h. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 48 publications
5
73
0
Order By: Relevance
“…GFP-HAS3 Protein Turnover Time in REKs-Cycloheximide caused ϳ50% reduction in hyaluronan synthesis in 4 h, a result in line with reports on cultured chondrocytes, mesothelioma cells, and orbital fibroblasts (23)(24)(25)(26). Although the reduction of hyaluronan synthesis can be due to protein targets of cycloheximide other than HAS, the present microscopic observations indicating a 4 -5 h turnover time of GFP-HAS3 were completely in line with a 2-3 h-half-life of HAS3 protein and the observed decline in hyaluronan synthesis.…”
Section: C-terminal Truncation Of Has3 and Exit From Er-supporting
confidence: 74%
See 1 more Smart Citation
“…GFP-HAS3 Protein Turnover Time in REKs-Cycloheximide caused ϳ50% reduction in hyaluronan synthesis in 4 h, a result in line with reports on cultured chondrocytes, mesothelioma cells, and orbital fibroblasts (23)(24)(25)(26). Although the reduction of hyaluronan synthesis can be due to protein targets of cycloheximide other than HAS, the present microscopic observations indicating a 4 -5 h turnover time of GFP-HAS3 were completely in line with a 2-3 h-half-life of HAS3 protein and the observed decline in hyaluronan synthesis.…”
Section: C-terminal Truncation Of Has3 and Exit From Er-supporting
confidence: 74%
“…If only overexpressed or GFP-HAS used the Golgi pathway, an inhibition by brefeldin A would not take place in non-transfected cells. Also, cycloheximide-induced inhibition of hyaluronan synthesis follows the same kinetics in non-transfected cells (23)(24)(25)(26) and the GFP-Has-transfected cells in this work.…”
Section: Gfp Label As An Indicator For Has Locations and Trafficsupporting
confidence: 51%
“…Moreover, TGF-/3 augments hyaluronic acid production by normal human mesothelial cells and fibroblasts [10,13]. These findings and our data suggest that TGF-/3 may greatly contribute to the formation of clinical features of MESO, characterized by thickening pleura on chest films and large amounts of hyaluronic acid in MPE in MESO.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, TGF-/? augments hyaluronic acid production by normal human mesothelial cells [13]. Although it is suggested that TGF-/?…”
Section: Introductionmentioning
confidence: 99%
“…To modulate the endogenous HA production, we treated PDAC cells with 4-methylumbelliferone (4-MU) which is a potent inhibitor of HA synthesis [19,20] and 12-O-tetradecanoyl-phorbol-13-acetate (TPA), a stimulator of HA synthesis through activating protein kinase C [21,22]. We also used another model of HA induction by coculturing PDAC cells with tumor-derived stromal fibroblasts [23].…”
Section: Introductionmentioning
confidence: 99%